Osteoporosis-Related Simultaneous Four Joints Fractures and Dislocation after a Seizure: A Case Report - Abdullah S. AlOmran (Journal of Osteoporosis)
A case of steroid-induced osteoporosis-related multiple fractures and dislocations are described after a seizure is reported. Patient had two years history of steroid use with no supplement or antiresorptive therapy. There was a delay in the diagnosis which affected an otherwise good outcome in such situations. It is recommended that patients on steroid should be given calcium, vitamin D, and an antiresorptive. Furthermore, a meticulous clinical examination is required in patients who are on steroids and suffer epileptic seizures to rule out skeletal injury.